THE INFLUENCE OF SOCIAL MEDIA ON GEN Z INVESTMENT DECISIONS IN APPLICATION-BASED CAPITAL MARKETS - Elok Maziyah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This study examines the influence of social media on Gen Z’s investment decisions in the Indonesian application-based capital market, with Intention of Use as an intervening variable. Utilising a quantitative research approach, the data were analysed using Structural Equation Modelling (SEM) with Partial Least Squares (PLS) analysis. The independent variables include Perceived Usefulness, Perceived Ease of Use, Perceived Risk, and Investment Knowledge, while the dependent variable is Investment Decisions, which are mediated by Intention to Use. The findings reveal that Intention of Use significantly impacts Gen Z’s investment decisions. Additionally, Perceived Usefulness, Perceived Ease of Use, and Investment Knowledge positively influence both investment decisions and the intention to use social media. Conversely, Perceived Risk has no significant effect on investment decisions or the intention to use social media. These results highlight the importance of social media as a strategic marketing tool for investment application developers. Developers are advised to focus on enhancing user experience and providing educational content to foster trust and knowledge, ultimately increasing Gen Z’s engagement and investment decisions in the application-based capital market.